2022
DOI: 10.3390/ijerph192214956
|View full text |Cite
|
Sign up to set email alerts
|

Positive Childhood Experiences Associate with Adult Flourishing Amidst Adversity: A Cross Sectional Survey Study with a National Sample of Young Adults

Abstract: The purpose of this study was to examine the prevalence of PCEs among young adults in Mainland China and the extent to which the cumulative number of PCEs moderates the associations between ACEs and flourishing in adulthood. Between August and November 2020, we used convenience and snowball sampling to recruit 9468 young adults, ages 18–35, enrolled in undergraduate or graduate programs at universities in Mainland China to participate in a survey, which included measures on flourishing, exposure to ACEs and PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 74 publications
0
8
1
Order By: Relevance
“…Although there is prior evidence to support a buffering effect of PCEs ( Elmore et al, 2020 ; Yu et al, 2022 ), our study found that the total score did not interact with the individual PCE domains. This suggests that the effect of PCEs may operate independently of ACEs to influence adult health outcomes, which is in line with other work ( Bethell et al, 2019 ; Lynch et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although there is prior evidence to support a buffering effect of PCEs ( Elmore et al, 2020 ; Yu et al, 2022 ), our study found that the total score did not interact with the individual PCE domains. This suggests that the effect of PCEs may operate independently of ACEs to influence adult health outcomes, which is in line with other work ( Bethell et al, 2019 ; Lynch et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Generally, it is posited that PCEs buffer the negative effect of ACEs on lifelong health ( Elmore et al, 2020 ; Liu et al, 2020 ; Yu et al, 2022 ; Zhang et al, 2021 ). Alternatively, PCEs may protect health independent of ACE exposure ( Bethell et al, 2019 ; Lynch et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it is considered an essential aspect of mental health promotion ( Burns et al, 2022 ). Previous studies have shown that experiencing parental warmth during childhood is significantly associated with Flourishing scores during mid-adulthood ( Chen et al, 2019 ); suggesting a link between childhood experiences and adulthood subjective well-being ( Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, 39% of adolescents have at least one type of ACE, and Chinese undergraduates with a history of ACEs are more likely to report symptoms of psychological distress and ultimately higher premature mortality than those without a history of ACEs [ 14 , 15 ]. Given the harmful effects of ACEs on health, recent studies have begun to identify protective factors that can help adolescents overcome the negative impacts of ACEs on mental health outcomes [ 16 , 17 ]. Indeed, positive self-awareness and relationship with caregivers, peers, and teachers are known as BCEs [ 18 ].…”
Section: Introductionmentioning
confidence: 99%